2015
DOI: 10.4103/0019-5049.158740
|View full text |Cite
|
Sign up to set email alerts
|

Is dexmedetomidine better than propofol and fentanyl combination in minor day care procedures? A prospective randomised double-blind study

Abstract: Background and Aims:The growing popularity and trend of day care (ambulatory) anaesthesia has led to the development of newer and efficient drug regimen. We decided to evaluate the efficacy of two drug regimens namely dexmedetomidine and propofol with midazolam and fentanyl for moderate sedation characteristics in minor surgical procedures in terms of analgesia, intra-operative sedation, haemodynamic stability and side effects related.Methods:Totally, 60 adult American Society of Anaesthesiologists class I-II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…[ 6 ] It has been successfully employed as a total anaesthetic agent in minor surgical procedures and in day-care minimally invasive procedures and other minor procedures facilitating early discharge. [ 7 8 9 ] It has been seen to improve post-operative analgesia following radical mastectomy, but there is a paucity of literature regarding its influence on early discharge of patients undergoing breast cancer surgery. [ 10 ] Lower POP, decrease rate of nausea and vomiting and early mobilization are factors that foster such surgeries on daycare basis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] It has been successfully employed as a total anaesthetic agent in minor surgical procedures and in day-care minimally invasive procedures and other minor procedures facilitating early discharge. [ 7 8 9 ] It has been seen to improve post-operative analgesia following radical mastectomy, but there is a paucity of literature regarding its influence on early discharge of patients undergoing breast cancer surgery. [ 10 ] Lower POP, decrease rate of nausea and vomiting and early mobilization are factors that foster such surgeries on daycare basis.…”
Section: Discussionmentioning
confidence: 99%
“…21 During the intraoperative period, regional neuraxial blockade with general anaesthesia was significantly lower the mean arterial blood pressure (MAP) and pulse rate. 22 Tomar et al (2015) found that haemodynamic stability was significantly greater in dexmedetomidine along with fentanyl and PCM as compared to fentanyl and PCM group. 23 In the present study we observed that the IL-6 level was significantly different between pre and post-operative in group III whereas, it was not significantly different between group I and group II.…”
Section: Discussionmentioning
confidence: 96%
“…22 Tomar et al (2015) found that haemodynamic stability was significantly greater in dexmedetomidine along with fentanyl and PCM as compared to fentanyl and PCM group. 23 In the present study we observed that the IL-6 level was significantly different between pre and post-operative in group III whereas, it was not significantly different between group I and group II. Similary, Li et al (2014) reported that the perioperative use of dexmedetomidine as an adjunct substantially decreases serum IL-6 levels.…”
Section: Discussionmentioning
confidence: 96%
“…Keterbatasan penggunaan BIS, yaitu tidak dapat memprediksi respons terhadap rangsangan nyeri dan penambahan opioid. 5,14 Penelitian ini didapatkan nilai BIS sebelum tindakan kuretase ( Tabel 2) 8,9,15 Hasil penelitian ini juga memperlihatkan perbedaan hasil pada MAP, laju nadi, dan saturasi oksigen pada kedua kelompok. Nilai MAP pada kedua kelompok terjadi penurunan dari data dasar, kelompok FP lebih rendah dibanding dengan kelompok D (Gambar 1), tetapi tidak berbeda bermakna secara klinis seperti hipertensi atau hipotensi pada pasien.…”
Section: Subjek Dan Metodeunclassified
“…Penurunan MAP pada kelompok FP disebabkan oleh penurunan tahanan sistemik vaskular, kontraktilitas jantung, dan aliran darah balik. 7,8,14 Hasil penelitian ini menunjukkan laju nadi (Gambar 2) pada kelompok deksmedetomidin lebih rendah dibanding kelompok fentanilpropofol, tetapi tidak berbeda bermakna secara klinis seperti bradikardia yang membutuhkan terapi tambahan pada pasien. 8,10,11 Penelitian ini sesuai dengan penelitian yang membandingkan deksmedetomidin dengan fentanil-propofol pada pasien yang dilakukan tindakan dilatasi dan kuretase dengan hasil pada kelompok deksmedetomidin itu terjadi perlambatan laju nadi, tidak terjadi desaturasi, dan juga MAP hampir sama dibanding dengan fentanil-propofol.…”
Section: Subjek Dan Metodeunclassified